A soldering filler metal and a soldering method for ceramics and high-temperature alloys
Patent Information
- Application Number
- CN202611384274.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]本发明旨在解决陶瓷与高温合金焊接导致的微裂纹萌生并扩展和陶瓷分解在钎缝中生成硅化物或低熔点脆性金属间化合物的问题
[0015]本发明的一种用于陶瓷与高温合金的焊接钎料及焊接方法的有益效果是:用于陶瓷与高温合金的焊接钎料,焊接过程中以预设的升温速度加热。当温度达到面心立方结构高熵合金基钎料的熔点时,该基钎料优先熔化,形成液态钎料,由于其中含有钛等活性元素,液态钎料能够有效润湿碳化硅陶瓷和镍基高温合金的表面,促进良好的冶金结合。随着温度进一步升高,液态的面心立方结构高熵合金基钎料中的钛元素开始与第二相钎料中的硼元素发生反应,由于硼粉的熔点较高,其在基体熔化后才开始反应,从而避免了过早的团聚。在液相或固液界面,钛和硼原位反应生成了细小的硼化钛晶须。这些晶须在焊缝中均匀弥散分布,形成增强相。随后,焊接部件以受控的降温速度冷却至室温。在冷却过程中,由于面心立方结构高熵合金基钎料的热膨胀系数高于第二相钎料,并且其本身具有良好的塑性,因此能够优先吸收因陶瓷与高温合金之间热膨胀失配而产生的残余应力,从而有效缓解应力集中。同时,原位生成的硼化钛晶须作为弥散强化相,能够有效阻碍裂纹的萌生和扩展,进一步提升焊缝的强度和韧性,大幅提升了接头的韧性和服役稳定性。由此,通过面心立方结构高熵合金基钎料的应力缓解能力和原位生成晶须的弥散强化作用,协同解决了热膨胀失配和脆性相生成的问题,获得了高强度和高稳定性的焊接接头。
Smart Images

Figure CN122913723A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of welding technology, and more specifically, to a brazing filler metal and welding method for ceramics and high-temperature alloys. Background Technology
[0002] Ceramic matrix composites (CMCs) have significant applications in high-temperature aerospace components, while high-temperature alloys (HTAs) serve as load-bearing structural materials. Reliable bonding between these two materials is a critical requirement in engineering practice. The core challenge of existing brazing technologies stems from the differences in the physicochemical properties of CMCs and HTAs. Firstly, their coefficients of thermal expansion differ significantly, leading to high residual thermal stress at the interface during welding cooling. This stress concentration zone, particularly on the CMC side, easily forms, causing microcrack initiation and propagation, severely weakening the joint's structural integrity. Secondly, to achieve effective wetting and metallurgical bonding of CMCs, conventional methods require the introduction of active elements such as titanium, zirconium, or hafnium. However, in the high-temperature liquid phase, these active elements readily react excessively with the ceramic matrix, inducing ceramic decomposition and generating silicides or low-melting-point brittle intermetallic compounds in the brazing seam. These brittle phases not only reduce joint strength but also impair its high-temperature service stability. Summary of the Invention
[0003] The present invention aims to solve the problems of microcrack initiation and propagation caused by welding ceramics to high-temperature alloys and the formation of silicides or low-melting-point brittle intermetallic compounds in the brazing seam due to ceramic decomposition.
[0004] To address the above problems, this invention provides a brazing filler metal for ceramics and high-temperature alloys and a welding method thereof.
[0005] In a first aspect, the present invention provides a welding filler metal for ceramics and high-temperature alloys, comprising a face-centered cubic high-entropy alloy-based filler metal with phase separation characteristics and a second phase filler metal, wherein the thermal expansion coefficient of the face-centered cubic high-entropy alloy-based filler metal is higher than that of the second phase filler metal, and the melting point of the face-centered cubic high-entropy alloy-based filler metal is lower than that of the second phase filler metal. Face-centered cubic high-entropy alloy-based solder and second-phase solder undergo in-situ reaction to produce whiskers during the soldering process; wherein the face-centered cubic high-entropy alloy-based solder includes one or more of Ti and V, and the second-phase solder includes one or more of B, Si and C.
[0006] Optionally, the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal can be uniformly mixed by vacuum arc melting or laser melting.
[0007] Optionally, the face-centered cubic high-entropy alloy-based solder includes one or more of AuCu-Ti, CuNi-Ti, AuCu-V, CuNi-V, Cu-Ti, and CoCrFeNiCu-Ti.
[0008] Optionally, the second phase solder includes one or more of B, SiC, and NbB2.
[0009] Optionally, the whiskers include one or more of TiB whiskers, TiC whiskers, Ti5Si3 whiskers, (Ti,Nb)B2 whiskers, VB2 whiskers, VB whiskers, V3Si whiskers, VSi2 whiskers, VC whiskers, and (V,Nb)B2 whiskers.
[0010] Optionally, the second phase solder may also include one or more of Mo and W.
[0011] Optionally, the whiskers also include one or more of Mo2TiB2 whiskers, W2TiB2 whiskers, TiMoB whiskers, TiWB whiskers, Mo2V8B2 whiskers, and W2V8B2 whiskers.
[0012] Optionally, the mass ratio of the face-centered cubic high-entropy alloy-based brazing filler metal to the second-phase brazing filler metal is 90:10 to 70:30.
[0013] Secondly, the present invention provides a method for welding ceramics to high-temperature alloys, comprising the following steps: S1: Take the brazing filler metal for ceramic and high-temperature alloy welding as described above, place it in a vacuum environment in the order of ceramic, brazing filler metal and high-temperature alloy, heat it to 300 ℃ to 500 ℃ at a heating rate of 8 ℃ / min to 15 ℃ / min and hold it at that temperature for more than 10 min. S2: Continue heating to the brazing temperature at a heating rate of 8 ℃ / min to 15 ℃ / min and hold until the brazing filler metal melts; S3: Cool down to 20°C to 400°C at a rate of 5°C / min to 10°C / min, and then furnace cool to room temperature.
[0014] Optionally, the brazing filler metal used for welding ceramics and high-temperature alloys is prepared into a paste-like filler metal using an adhesive, wherein the adhesive accounts for 10 wt% to 20 wt% of the total mass of the paste-like filler metal, and the adhesive includes one or more of rosin-based gum, cellulose-based gum, terpineol and anhydrous ethanol.
[0015] The beneficial effects of the brazing filler metal for ceramics and superalloys and the welding method thereof according to the present invention are as follows: the brazing filler metal for ceramics and superalloys is heated at a preset heating rate during the welding process. When the temperature reaches the melting point of the face-centered cubic structure high-entropy alloy-based brazing filler metal, the base brazing filler metal melts preferentially to form a liquid brazing filler metal. Since it contains active elements such as titanium, the liquid brazing filler metal can effectively wet the surfaces of silicon carbide ceramics and nickel-based superalloys, promoting good metallurgical bonding. As the temperature further rises, the titanium element in the liquid face-centered cubic structure high-entropy alloy-based brazing filler metal begins to react with the boron element in the second-phase brazing filler metal. Since boron powder has a relatively high melting point, it starts to react only after the base material melts, thereby avoiding premature agglomeration. At the liquid phase or solid-liquid interface, titanium and boron react in-situ to generate fine titanium boride whiskers. These whiskers are uniformly and dispersedly distributed in the weld seam, forming a reinforcing phase. Subsequently, the welded component is cooled to room temperature at a controlled cooling rate. During the cooling process, since the face-centered cubic structure high-entropy alloy-based brazing filler metal has a higher thermal expansion coefficient than the second-phase brazing filler metal and itself has good plasticity, it can preferentially absorb the residual stress generated by the thermal expansion mismatch between the ceramic and the superalloy, thereby effectively relieving stress concentration. At the same time, the in-situ generated titanium boride whiskers, as a dispersion-strengthening phase, can effectively hinder the initiation and propagation of cracks, further improve the strength and toughness of the weld seam, and greatly enhance the toughness and service stability of the joint. Therefore, through the stress relief capability of the face-centered cubic structure high-entropy alloy-based brazing filler metal and the dispersion strengthening effect of the in-situ generated whiskers, the problems of thermal expansion mismatch and brittle phase formation are solved synergistically, and a welded joint with high strength and high stability is obtained. Brief Description of the Drawings
[0016] Figure 1 is a schematic flow diagram of the welding method for ceramics and superalloys according to an embodiment of the present invention; Figure 2 is an electron microscope schematic diagram of the joint of Example 1; Figure 3 is Figure 2 an enlarged view of portion A; Figure 4 is Figure 2 an enlarged view of portion B; Figure 5 is an electron microscope schematic diagram of the joint of Example 4; Figure 6 wherein (a) is a BSE photograph of the joint of Comparative Example 1; Figure 6 wherein (b) is a BSE photograph of the joint of Comparative Example 2; Figure 6 wherein (c) is a BSE photograph of the joint of Comparative Example 3; Figure 6 wherein (d) is Figure 6 an enlarged view of part d in (a); Figure 6 (e) is Figure 6 Enlarged view of point e in (b); Figure 6 (f) is Figure 6 Enlarged view of point f in (c). Detailed Implementation
[0017] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Although some embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the accompanying drawings and embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0018] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this invention's description is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. As used herein, the term "comprising" and its variations are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the description below. In the description of this application, unless otherwise stated, "a plurality of" means two or more.
[0019] In related technologies, brazing filler metal systems containing active elements are often used, such as gold-copper-titanium, copper-nickel-titanium, gold-copper-vanadium, copper-nickel-vanadium, copper-titanium, and cobalt-chromium-iron-nickel-copper-titanium, in an attempt to relieve interfacial stress by utilizing the plasticity and toughness of face-centered cubic materials. However, such methods generally suffer from defects such as insufficient high-temperature resistance and easy agglomeration of intermetallic compounds in the weld, and cannot simultaneously achieve wettability, stress relief, and interfacial stability.
[0020] To address the problems existing in the aforementioned related technologies, embodiments of the present invention provide a brazing filler metal for ceramics and high-temperature alloys and a welding method thereof.
[0021] An embodiment of the present invention provides a welding filler metal for ceramics and high-temperature alloys, comprising a face-centered cubic high-entropy alloy-based filler metal with phase separation characteristics and a second phase filler metal. The thermal expansion coefficient of the face-centered cubic high-entropy alloy-based filler metal is higher than that of the second phase filler metal, and the melting point of the face-centered cubic high-entropy alloy-based filler metal is lower than that of the second phase filler metal. Face-centered cubic high-entropy alloy-based solder and second-phase solder undergo in-situ reaction to produce whiskers during the soldering process; wherein the face-centered cubic high-entropy alloy-based solder includes one or more of Ti and V, and the second-phase solder includes one or more of B, Si and C.
[0022] Specifically, ceramics (CMC) are polycrystalline solid materials made from inorganic non-metallic materials (natural minerals or artificially synthesized compounds) through molding and high-temperature sintering. They are known as the three major solid materials along with metals and polymers. They are mainly made from natural silicates such as clay, quartz, and feldspar, such as SiC ceramics, SiCf / SiC ceramics, and Cf / SiC ceramics.
[0023] Superalloys are a class of high-performance metallic materials with iron, nickel, and cobalt as the base material that can serve for a long time at high temperatures above 600°C and under certain stress. Examples include nickel-based superalloys GH3536, nickel-based superalloys GH3039, and cobalt-based superalloys GH5188.
[0024] Face-centered cubic (FCC) high-entropy alloy-based brazing filler metals are alloys with a face-centered cubic crystal structure, characterized by the presence of multiple high-concentration principal components. This structure typically imparts good plasticity and toughness to the material, helping to alleviate stress in brazed joints. As the matrix material, it constitutes the continuous phase of the brazing filler metal.
[0025] Phase separation refers to the phenomenon of separation between different phases in face-centered cubic high-entropy alloy-based solders during processing or service. This characteristic can be used to control the microstructure and properties, such as forming a tough matrix with dispersed reinforcing phases, thereby improving the overall performance of the solder.
[0026] Second-phase brazing filler metal refers to an additional component in the brazing filler metal system that differs from face-centered cubic high-entropy alloy-based brazing filler metals. Second-phase brazing filler metals are designed to react with the matrix or other elements during the welding process to form a reinforcing phase or adjust the overall properties of the brazed joint.
[0027] Whiskers are microscopic needle-like or fibrous single crystals with a high aspect ratio. In the field of brazing, their in-situ formation in the weld can significantly provide strengthening and toughening effects, improving joint performance by hindering crack propagation and dispersing stress.
[0028] The coefficient of thermal expansion is a physical quantity that describes the degree to which a material expands or contracts with changes in temperature. In brazing dissimilar materials such as ceramics and high-temperature alloys, the difference in the coefficient of thermal expansion can lead to significant residual stress after cooling.
[0029] Melting point is the temperature at which a solid material transforms into a liquid state. In multi-component brazing filler metal systems, the relative melting points of different components affect the melting sequence and flow behavior during the brazing process.
[0030] In-situ formation refers to the formation of whiskers directly within the weld seam during the brazing process, rather than being added beforehand. In-situ formation typically enables the formation of finer, more uniformly distributed reinforcing phases, thereby more effectively enhancing mechanical properties.
[0031] Face-centered cubic (FCC) high-entropy alloy-based solders can include titanium and / or vanadium. These elements, as active components, can enhance the wettability of the solder to ceramic materials and participate in subsequent interfacial reactions. For example, an appropriate amount of titanium can be added to the high-entropy alloy matrix to enhance its affinity with the ceramic surface. Alternatively, vanadium can be introduced, as it exhibits good activity at high temperatures and helps form a stable interfacial phase.
[0032] The second-phase solder can include boron, silicon, and / or carbon. These elements are key components in the formation of high-strength, high-hardness whiskers. For example, boron powder can be used as the second-phase solder, reacting with active elements in face-centered cubic high-entropy alloy-based solders during the soldering process to form boride whiskers. Alternatively, silicon powder can be introduced to react with active elements to form silicide whiskers. Furthermore, carbon powder can also be used as the second-phase solder, reacting with active elements to form carbide whiskers.
[0033] In this embodiment, the solder used for welding ceramics and high-temperature alloys is heated at a preset heating rate during the welding process. When the temperature reaches the melting point of the face-centered cubic high-entropy alloy-based solder, the solder melts preferentially, forming a liquid solder. Due to the presence of active elements such as titanium, the liquid solder effectively wets the surfaces of silicon carbide ceramics and nickel-based high-temperature alloys, promoting good metallurgical bonding. As the temperature further increases, the titanium element in the liquid face-centered cubic high-entropy alloy-based solder begins to react with the boron element in the second-phase solder. Because the boron powder has a high melting point, it only begins to react after the matrix melts, thus avoiding premature agglomeration. At the liquid phase or solid-liquid interface, titanium and boron react in situ to generate fine titanium boride whiskers. These whiskers are uniformly dispersed in the weld, forming a reinforcing phase. Subsequently, the welded components are cooled to room temperature at a controlled cooling rate. During the cooling process, the face-centered cubic high-entropy alloy-based brazing filler metal, with its higher coefficient of thermal expansion than the second-phase filler metal and its excellent plasticity, preferentially absorbs the residual stress caused by the thermal expansion mismatch between the ceramic and the high-temperature alloy, effectively alleviating stress concentration. Simultaneously, the in-situ generated titanium boride whiskers, acting as a dispersed strengthening phase, effectively inhibit crack initiation and propagation, further enhancing the strength and toughness of the weld and significantly improving the joint's toughness and service stability. Thus, by combining the stress-relieving ability of the face-centered cubic high-entropy alloy-based brazing filler metal with the dispersed strengthening effect of the in-situ generated whiskers, the problems of thermal expansion mismatch and brittle phase formation are synergistically solved, resulting in a high-strength and high-stability welded joint.
[0034] In some specific embodiments, the particle size of the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal is precisely controlled within the range of 15 μm to 53 μm, effectively solving the problem of easy agglomeration of fine particles due to high surface energy. This particle size range avoids the risk of agglomeration caused by excessively small particles, ensuring uniform dispersion of the second-phase brazing filler metal in the face-centered cubic high-entropy alloy-based brazing filler metal. Simultaneously, it prevents problems such as uneven mixing and insufficient dissolution and diffusion caused by excessively large particles, enabling efficient and uniform distribution of the second-phase brazing filler metal during melting and rapid cooling, promoting the formation of an ideal phase-separated structure. This uniform dispersion allows the composite brazing filler metal to more effectively control thermal stress during welding, reduce stress concentration at the joint interface, and effectively strengthen the weld, thereby significantly improving the overall performance of the composite brazing filler metal and the reliability of the welded joint.
[0035] Optionally, the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal can be uniformly mixed by vacuum arc melting or laser melting.
[0036] Specifically, vacuum arc melting is a method of melting metallic materials using an electric arc as a heat source under vacuum or inert gas protection. This method effectively avoids oxidation or gas absorption during the melting process, while the high temperature generated by the arc promotes the full diffusion of alloying elements, thereby ensuring a highly uniform mixture between different components. As a specific implementation method, a water-cooled copper crucible can be used as the melting vessel. After evacuating to a high vacuum level, a high-purity inert gas (such as argon) is introduced for protection. By adjusting the arc current and melting time, the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal are fully melted and mixed.
[0037] Laser melting is a method that uses a high-energy-density laser beam as a heat source to rapidly melt and solidify materials locally. This method features concentrated energy, rapid heating, and a small heat-affected zone, enabling precise control of the molten pool and effectively suppressing elemental segregation, thus ensuring the consistency and stability of the melting process. For example, a high-power fiber laser or Nd:YAG laser can be used to focus the laser beam onto the surface of the material to be melted. Scanning the laser beam rapidly melts and mixes the material, and the process is carried out under an inert gas atmosphere to prevent oxidation.
[0038] In this optional embodiment, the use of vacuum arc melting or laser melting ensures uniform mixing of the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal during the melting process. In the basic scheme, the thermal expansion coefficient of the face-centered cubic high-entropy alloy-based brazing filler metal is higher than that of the second-phase brazing filler metal, and its melting point is lower than that of the second-phase brazing filler metal. This design aims to alleviate residual stress in the weld joint through the difference in thermal expansion between the two phases, and to enhance joint performance by generating whiskers through in-situ reaction of the two phases during the welding process. However, if the brazing filler metal components are not mixed uniformly, the aforementioned difference in thermal expansion coefficients cannot be stably reflected throughout the weld, and the in-situ generation of whiskers will also become unstable due to uneven distribution of reactants. Vacuum arc melting or laser melting can effectively overcome the elemental segregation and inhomogeneity problems that may occur in traditional melting methods. Vacuum arc melting is carried out in a vacuum or inert atmosphere, avoiding oxidation and the introduction of impurities. At the same time, the high energy density of the arc promotes the full melting and diffusion of each component, ensuring macroscopic and microscopic uniformity. Laser melting, with its precise energy control and rapid melting and solidification characteristics, enables fine mixing in localized areas, further reducing the possibility of elemental segregation. This uniform mixing allows the brazing filler metal to stably exhibit the expected thermal expansion behavior during subsequent welding, effectively mitigating the thermal stress mismatch between the ceramic and high-temperature alloy. Simultaneously, the uniformly distributed reaction components ensure the uniform and controllable in-situ formation of whiskers within the weld, forming a dispersed reinforcing phase and significantly improving the mechanical properties and reliability of the weld. Therefore, this method, by precisely controlling the brazing filler metal melting process, provides a stable material basis for thermal stress relief and in-situ whisker formation during subsequent welding, thereby significantly improving the overall performance and service stability of the ceramic-high-temperature alloy welded joint.
[0039] In some specific embodiments, the vacuum arc melting method employs a non-consumable tungsten electrode arc (NCA) melting process, with the current controlled between 400A and 550A. Using a NCA effectively avoids contamination of the melt by the electrode material, ensuring the purity of the solder composition. Simultaneously, the stable arc provided by the NCA makes the heat input more uniform and controllable, significantly reducing the problem of uneven heat distribution caused by arc instability. Precisely controlling the current within the range of 400A to 550A ensures that the heat input during the melting process can fully melt the face-centered cubic high-entropy alloy-based solder and the second-phase solder, promoting their uniform mixing, while effectively avoiding localized overheating and material splashing, thereby reducing the risk of second-phase solder agglomeration. The combination of the above technical solutions enables a more thorough and uniform mixing of the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal during the melting process, laying a solid foundation for the subsequent rapid cooling steps. Ultimately, this significantly improves the phase separation uniformity and overall performance of the composite brazing filler metal, thereby effectively solving the problems of uneven mixing and agglomeration caused by improper selection of melting parameters.
[0040] In some specific embodiments, the laser power of the laser melting method is 70 W to 400 W, the scanning speed is 70 mm / s to 1800 mm / s, the scanning spacing is 50 μm to 140 μm, and the layer thickness is 20 μm to 50 μm. By precisely controlling the laser power, scanning speed, scanning spacing, and layer thickness of the laser melting method, this application can effectively optimize the energy input and spatial distribution during the melting process. Specifically, controlling the laser power within the range of 70 W to 400 W provides sufficient energy to fully melt the face-centered cubic high-entropy alloy-based solder and the second-phase solder, avoiding cold spots or unfused areas, while also effectively preventing excessive material evaporation, splashing, or thermal damage due to excessive power. Simultaneously, by setting the scanning speed to 70 mm / s to 1800 mm / s, the formation and movement rate of the molten pool can be balanced, avoiding agglomeration of second-phase particles caused by localized overheating due to excessively slow speed, or uneven cooling due to excessively fast speed, which affects the mixing uniformity. Furthermore, controlling the scanning spacing between 50 μm and 140 μm ensured uniform laser beam coverage of the material surface, reducing heat accumulation in overlapping areas and promoting thorough mixing of the face-centered cubic high-entropy alloy-based solder and the second-phase solder. Finally, controlling the layer thickness between 20 μm and 50 μm ensured a suitable deposition thickness, which facilitated uniform heat transfer during layer-by-layer melting, further improving melting efficiency and phase separation stability. This synergistic optimization of parameters significantly improved the uniformity of the composite solder, effectively suppressing the agglomeration of second-phase particles. This ensured a stable and effective dispersion of the second-phase solder within the face-centered cubic high-entropy alloy-based solder, laying a solid foundation for the subsequent phase separation process. Ultimately, this helped reduce joint thermal stress, control interfacial stress distribution, and improve the performance of the welded joint.
[0041] Optionally, the face-centered cubic high-entropy alloy-based solder includes one or more of AuCu-Ti, CuNi-Ti, AuCu-V, CuNi-V, Cu-Ti, and CoCrFeNiCu-Ti.
[0042] Specifically, the composition of face-centered cubic (FCC) high-entropy alloy-based solders is one of the key technical features of this application. Among them, alloy systems such as AuCu-Ti, CuNi-Ti, AuCu-V, CuNi-V, and Cu-Ti are generally known for their good plasticity, ductility, and wettability to ceramic materials. For example, AuCu and CuNi, as the matrix, provide excellent toughness and thermal conductivity, while Ti or V, as active elements, effectively promote the metallurgical bonding between the solder and the ceramic interface. These alloy systems can maintain a relatively stable face-centered cubic crystal structure at high temperatures, thus providing good stress relief during welding. Furthermore, CoCrFeNiCu-Ti is a typical face-centered cubic high-entropy alloy, whose unique "cocktail effect" gives it excellent strength, toughness, thermal stability, and oxidation resistance at high temperatures. This alloy system, through the synergistic effect of multiple principal elements, can effectively suppress the formation and growth of brittle phases and provide a wider service temperature range. The selection of these alloys aims to optimize the overall performance of the solder to meet the stringent requirements of heterojunction between ceramics and high-temperature alloys.
[0043] In this optional embodiment, by precisely defining the specific composition of the face-centered cubic high-entropy alloy-based solder, it can more effectively solve the problems of insufficient temperature resistance and intermetallic compound agglomeration in the prior art when working together with the aforementioned second-phase solder. Specifically, the selected alloys such as AuCu-Ti, CuNi-Ti, AuCu-V, CuNi-V, Cu-Ti, and CoCrFeNiCu-Ti can maintain the stability of their face-centered cubic crystal structure during welding, thereby providing continuous plastic deformation capability and effectively alleviating residual thermal stress caused by the difference in thermal expansion coefficients between ceramics and high-temperature alloys. At the same time, the active elements Ti or V in these alloys can more precisely control the kinetics of the interfacial reaction during the in-situ formation of whiskers with B, Si, or C in the second-phase solder, avoiding excessive consumption of active elements or the formation of large-sized, agglomerated brittle intermetallic compounds. In particular, high-entropy alloys such as CoCrFeNiCu-Ti exhibit a multi-element synergistic effect that further enhances the high-temperature resistance and microstructure stability of the brazing filler metal matrix. This ensures a uniform and fine weld microstructure with dispersed whisker distribution during high-temperature brazing, significantly improving joint strength and high-temperature reliability. This optimized brazing filler metal composition, combined with the in-situ whisker reinforcement mechanism, allows the filler metal to effectively suppress harmful reactions and the formation of brittle phases while ensuring sufficient wetting of the ceramic and reliable metallurgical connection. This overcomes the limitations of traditional brazing filler metals in terms of temperature resistance and weld microstructure control.
[0044] Optionally, the second phase solder includes one or more of B, SiC, and NbB2.
[0045] Specifically, boron (B), as a non-metallic element, exhibits high reactivity at high temperatures and readily reacts with transition metals (such as Ti and V) to form stable borides. During brazing, boron can act as a reactant, promoting the in-situ formation of boride whiskers, such as TiB whiskers or VB whiskers. These boride whiskers possess high hardness and high modulus, effectively enhancing the mechanical properties of the brazed joint and helping to alleviate thermal stress.
[0046] SiC is a covalent compound with excellent high-temperature strength, hardness, and corrosion resistance. Introducing SiC into brazing filler metals can serve as both a silicon and carbon source. During high-temperature brazing, SiC can decompose and react with active elements (such as Ti and V) in face-centered cubic high-entropy alloy-based filler metals, generating in-situ silicide whiskers (such as Ti5Si3 whiskers, V3Si whiskers, and VSi2 whiskers) or carbide whiskers (such as TiC whiskers and VC whiskers). These whiskers can further refine the brazed joint microstructure, improving its strength and toughness.
[0047] NbB2 is a transition metal boride with a high melting point and high hardness. When used as a component of the second-phase solder, it can exist directly as a dispersed phase during soldering, or react at high temperatures with other elements in face-centered cubic high-entropy alloy-based solders to form in-situ composite boride whiskers, such as (Ti,Nb)B2 whiskers or (V,Nb)B2 whiskers. The introduction of NbB2 helps improve the high-temperature strength and creep resistance of the solder joint, while its high hardness also strengthens the joint.
[0048] In this optional embodiment, the mechanism for in-situ whisker generation between the face-centered cubic (FCC) high-entropy alloy-based solder and the second-phase solder during welding is optimized by defining the specific composition of the second-phase solder, namely, including one or more of B, SiC, and NbB2. The FCC high-entropy alloy-based solder has a higher coefficient of thermal expansion than the second-phase solder and a lower melting point, which provides favorable conditions for in-situ whisker generation. When the solder melts under heat during welding, the FCC high-entropy alloy-based solder melts first and wets the substrate, while B, SiC, or NbB2 in the second-phase solder reacts with active elements (such as Ti and V) in the FCC high-entropy alloy-based solder in the liquid phase. Specifically, B can react rapidly with the active elements to form high-hardness boride whiskers, such as TiB or VB. SiC provides silicon and carbon atoms, which react with the active elements at high temperatures to generate silicide whiskers (such as Ti5Si3) or carbide whiskers (such as TiC). NbB2, acting as a pre-phase or reactive phase, can form composite boride whiskers (such as (Ti,Nb)B2). These whiskers grow in situ within the brazing joint, forming a dispersed reinforcing phase network. These in-situ generated whiskers not only bond well with the matrix, but their unique morphology and distribution effectively inhibit crack propagation and improve the fracture toughness of the brazing joint. Simultaneously, the formation and distribution of these whiskers allow for more precise control of the overall thermal expansion coefficient of the brazing joint, effectively mitigating the thermal expansion mismatch between the brazing joint and the ceramic and high-temperature alloy. In this way, this solution optimizes the whisker formation process by precisely controlling the composition of the second-phase brazing filler metal, while ensuring sufficient wetting of the ceramic and reliable metallurgical connection. This effectively suppresses harmful interfacial reactions and the formation of brittle phases, thereby improving the joint's strength and service stability.
[0049] Optionally, the whiskers include one or more of TiB whiskers, TiC whiskers, Ti5Si3 whiskers, (Ti,Nb)B2 whiskers, VB2 whiskers, VB whiskers, V3Si whiskers, VSi2 whiskers, VC whiskers, and (V,Nb)B2 whiskers.
[0050] Specifically, these whiskers are generated in situ during the soldering process, and their type and composition are crucial for optimizing the weld microstructure and alleviating residual stress. TiB whiskers, TiC whiskers, and Ti5Si3 whiskers are formed based on the reaction of titanium with boron, carbon, and silicon in the solder. These whiskers possess high hardness and strength, effectively dispersing stress and existing as reinforcing phases in the weld. For example, TiB whiskers can appear as needles or rods, uniformly distributed in the matrix, hindering crack propagation; TiC whiskers exist in the form of fine particles, improving the overall strength of the weld. VB2 whiskers, VB whiskers, V3Si whiskers, VSi2 whiskers, and VC whiskers are formed based on the reaction of vanadium with boron, silicon, and carbon in the solder. These whiskers provide strength while maintaining a certain degree of toughness, helping to alleviate brittleness. For example, VB2 whiskers and VC whiskers can act as dispersed reinforcing phases, improving the weld's creep resistance; V3Si whiskers and VSi2 whiskers can improve the weld's ductility and toughness, preventing brittle fracture. (V,Nb)B2 whiskers are formed by the reaction of titanium and vanadium with niobium and boron in the solder. Introducing niobium can further improve the heat resistance and interfacial bonding performance of the whiskers with the matrix, enhancing their stability at high temperatures. For example, (V,Nb)B2 whiskers can form composite borides with good thermal stability, improving the high-temperature mechanical properties of the weld.
[0051] In this optional embodiment, by pre-setting an element combination capable of in-situ generating specific types of whiskers in the brazing filler metal, the Ti and V elements in the face-centered cubic high-entropy alloy-based brazing filler metal react with the B, Si, and C elements in the second-phase brazing filler metal, as well as any Nb elements that may be present, during the welding process, thereby generating the aforementioned specific types of whiskers in situ in the weld. These whiskers, such as TiB whiskers, TiC whiskers, Ti5Si3 whiskers, (V,Nb)B2 whiskers, VB2 whiskers, VB whiskers, V3Si whiskers, VSi2 whiskers, VC whiskers, and (V,Nb)B2 whiskers, due to their unique crystal structure and excellent mechanical properties, can serve as effective dispersed strengthening phases, uniformly distributed in the weld matrix. They can effectively hinder dislocation movement and crack propagation, thereby significantly improving the strength and toughness of the weld. At the same time, the formation of these whiskers can consume some active elements, inhibit the excessive growth and agglomeration of harmful brittle intermetallic compounds, and avoid the problem of brittle phase formation caused by uncontrolled interfacial reactions. In addition, the presence of these whiskers can further optimize the weld structure through pinning effect and grain refinement, and effectively disperse the residual thermal stress caused by the difference in thermal expansion coefficients between ceramics and high-temperature alloys, thereby alleviating stress concentration and improving the overall reliability and high-temperature service performance of the joint.
[0052] Optionally, the second phase solder may also include one or more of Mo and W.
[0053] Specifically, molybdenum (Mo) is a refractory metal with a high melting point, high strength, and high hardness, exhibiting excellent high-temperature performance and corrosion resistance. Introducing Mo into solder can increase its melting point and high-temperature strength, and it participates in the formation of highly stable intermetallic compounds, carbides, or borides. This can be achieved by adding pure Mo powder, Mo alloy powder, or Mo-containing compounds as a component of the second-phase solder.
[0054] Tungsten (W) is a refractory metal with an extremely high melting point and hardness, exhibiting excellent high-temperature strength, wear resistance, and creep resistance. Introducing W into brazing filler metal can significantly improve the high-temperature stability and mechanical properties of the brazing seam, and promote the formation of more stable and finer whiskers. This can be achieved by adding pure W powder, W alloy powder, or W-containing compounds as a component of the second-phase brazing filler metal.
[0055] In this optional embodiment, by adding one or more of Mo and W to the second-phase solder, a more complex whisker structure can be formed, enhancing the dispersion strengthening effect of the brazed joint and solving the problem of insufficient whisker temperature resistance in the original solution. Specifically, during the welding process, the face-centered cubic high-entropy alloy-based solder with phase separation characteristics reacts with the second-phase solder to generate whiskers in situ. Based on this, Mo and W introduced into the second-phase solder act as additional active elements, synergistically interacting with Ti and V in the face-centered cubic high-entropy alloy-based solder and B, Si, and C in the second-phase solder to promote the formation of composite whiskers with higher thermodynamic stability and higher melting points, such as Mo2TiB2 whiskers and W2V8B2 whiskers. These whiskers formed with the participation of Mo and W exhibit superior high-temperature stability and anti-agglomeration ability, and can more effectively suppress harmful interfacial reactions and the formation of brittle phases. In this way, the dispersion strengthening effect inside the brazed joint is more stably maintained at high temperatures, thereby improving the strength and service reliability of the joint under high-temperature conditions.
[0056] Optionally, the whiskers also include one or more of Mo2TiB2 whiskers, W2TiB2 whiskers, TiMoB whiskers, TiWB whiskers, Mo2V8B2 whiskers, and W2V8B2 whiskers.
[0057] Specifically, Mo2TiB2 whiskers are boride whiskers that are typically formed in situ through reactions in systems containing Mo, Ti, and B elements. They possess high hardness, high melting point, and good thermal stability, and can be dispersed as a reinforcing phase in welds to effectively improve the mechanical properties and high-temperature strength of welds.
[0058] W2TiB2 whiskers are boride whiskers similar to Mo2TiB2 whiskers, formed in systems containing W, Ti, and B elements. They also possess excellent high-temperature strength and creep resistance, which can further enhance the structural stability of welds at extreme temperatures. By refining grains and hindering dislocation movement, they improve the overall toughness of the material.
[0059] TiMoB whiskers are composite boride whiskers composed of Ti, Mo, and B elements. Their specific stoichiometric ratio may vary depending on the reaction conditions, but their core function is to utilize the synergistic effect of Ti and Mo to form a reinforcing phase with good interfacial bonding in the weld, which helps to optimize the interfacial reaction and reduce the formation of brittle intermetallic compounds.
[0060] TiWB whiskers are composite boride whiskers composed of Ti, W, and B elements. Similar to TiMoB whiskers, TiWB whiskers form a reinforcing phase with high strength and good thermal stability in the weld through the synergistic effect of Ti and W, which can effectively inhibit the growth of harmful phases and improve the microstructure uniformity of the weld.
[0061] Mo2V8B2 whiskers are boride whiskers containing Mo, V, and B elements. When V element is present in face-centered cubic high-entropy alloy-based solders, their formation can fully utilize the V element in the system, combining with Mo and B to form a stable reinforcing phase. This helps to achieve uniform dispersion strengthening in the weld, improving the tensile strength and fatigue resistance of the weld.
[0062] W2V8B2 whiskers are boride whiskers containing W, V, and B elements. Similar to Mo2V8B2 whiskers, the formation of W2V8B2 whiskers can utilize the V element in the system to combine with W and B to form a reinforcing phase with excellent high-temperature performance. This can further improve the mechanical properties of the weld in high-temperature environments and effectively resist creep and oxidation.
[0063] In this optional embodiment, by introducing Mo and W elements into the second-phase solder, these elements undergo complex in-situ reactions with Ti and V in the face-centered cubic high-entropy alloy-based solder and B, Si, and C in the second-phase solder during the welding process. These reactions occur in the high-temperature liquid phase and, with cooling, form various specific whiskers such as Mo2TiB2 whiskers, W2TiB2 whiskers, TiMoB whiskers, TiWB whiskers, Mo2V8B2 whiskers, and W2V8B2 whiskers. These whiskers exist in the weld as dispersed reinforcing phases, combining with the good plasticity and toughness inherent in the face-centered cubic high-entropy alloy-based solder itself to jointly enhance the weld microstructure. The introduction of Mo and W elements not only diversifies the types of whiskers formed but also generally results in higher thermal stability, hardness, and strength. For example, Mo2TiB2 and W2TiB2 whiskers effectively resist creep at high temperatures, while TiMoB and TiWB whiskers optimize interfacial reactions and reduce the formation of brittle intermetallic compounds. Simultaneously, the formation of Mo2V8B2 and W2V8B2 whiskers fully utilizes the V element in the face-centered cubic high-entropy alloy-based solder, ensuring uniform and efficient dispersion strengthening throughout the weld. This synergistic strengthening mechanism of multiple whisker types can more effectively alleviate residual thermal stress concentration caused by the difference in thermal expansion coefficients between ceramics and high-temperature alloys, and inhibit harmful interfacial reactions and the formation of brittle phases, thereby significantly improving the strength, toughness, and high-temperature service stability of the joint.
[0064] Optionally, the mass ratio of the face-centered cubic high-entropy alloy-based brazing filler metal to the second-phase brazing filler metal is 90:10 to 70:30.
[0065] In this optional embodiment, the face-centered cubic (FCC) high-entropy alloy-based brazing filler metal has a high coefficient of thermal expansion and a low melting point. During brazing, it melts first to form a continuous phase, providing good plasticity and stress relief for the weld. The second-phase brazing filler metal has a low coefficient of thermal expansion and a high melting point. After the FCC high-entropy alloy-based brazing filler metal melts, the active elements (such as B, Si, C) in the second-phase brazing filler metal react in situ with the active elements (such as Ti, V) in the FCC high-entropy alloy-based brazing filler metal to generate whiskers with reinforcing properties. By controlling the mass ratio of the FCC high-entropy alloy-based brazing filler metal between 70% and 90%, its dominant position as a continuous phase is ensured, effectively alleviating the thermal expansion mismatch stress between the ceramic and the high-temperature alloy. At the same time, controlling the mass ratio of the second-phase brazing filler metal between 10% and 30% ensures sufficient reactants to generate an appropriate amount of whiskers. These whiskers are uniformly dispersed in the weld, effectively inhibiting harmful interfacial reactions and refining and strengthening the weld microstructure. This optimized ratio allows the brazing filler metal to form a weld that combines ductility, toughness, and strength while ensuring good wettability and metallurgical bonding. This effectively solves the problem of whisker imbalance caused by improper brazing filler metal ratio and improves the overall performance of the brazed joint.
[0066] In some specific embodiments, the second phase of the solder accounts for 10 wt% to 20 wt% of the total solder mass. If the mass ratio of the second phase of the solder exceeds 30%, it is easy to cause poor solder flowability and decreased wettability.
[0067] like Figure 1 As shown, another embodiment of the present invention provides a welding method for ceramics and high-temperature alloys, comprising the following steps: S1: Take the brazing filler metal for ceramic and high-temperature alloy welding as described above, place it in a vacuum environment in the order of ceramic, brazing filler metal and high-temperature alloy, heat it to 300 ℃ to 500 ℃ at a heating rate of 8 ℃ / min to 15 ℃ / min and hold it at that temperature for more than 10 min. S2: Continue heating to the brazing temperature at a heating rate of 8 ℃ / min to 15 ℃ / min and hold until the brazing filler metal melts; S3: Cool down to 20°C to 400°C at a rate of 5°C / min to 10°C / min, and then furnace cool to room temperature.
[0068] In this embodiment, the dual objectives of stress relief and interface optimization are achieved through the coordinated control of temperature parameters. During the cooling process, the high plasticity of the FCC continuous phase in the brazing filler metal preferentially absorbs the residual stress caused by thermal expansion mismatch, while the dispersed second phase regulates the local strain distribution through its low expansion characteristics, effectively suppressing stress concentration. Furthermore, the gradient cooling process significantly reduces the interfacial reaction kinetic rate, avoiding the formation of brittle phases due to excessive diffusion of active elements, and ensuring the uniform and dispersed distribution of the strengthening phase in the weld microstructure. Through the above technical solution, not only is the cracking problem caused by thermal expansion mismatch solved, but the formation of brittle intermetallic compounds at the interface is also fundamentally suppressed, ultimately resulting in a ceramic / high-temperature alloy welded joint with high strength and excellent high-temperature service stability, particularly suitable for reliable connections of high-temperature components such as aero-engines.
[0069] Optionally, the brazing filler metal used for welding ceramics and high-temperature alloys is prepared into a paste-like filler metal using an adhesive, wherein the adhesive accounts for 10 wt% to 20 wt% of the total mass of the paste-like filler metal, and the adhesive includes one or more of rosin-based gum, cellulose-based gum, terpineol and anhydrous ethanol.
[0070] Specifically, the preparation of solder in paste form for welding ceramics and high-temperature alloys refers to mixing solder powder with a suitable binder system to form a paste with a certain viscosity and thixotropic properties. This preparation method can significantly improve the application method and uniformity of the solder at the welding interface. For example, a uniformly dispersed paste can be obtained by thoroughly mixing and grinding solder powder with components such as organic binders and solvents; or, advanced technologies such as spray drying or freeze drying can be used to transform solder slurry into a paste with specific rheological characteristics to meet the needs of different application scenarios. In the paste solder, the binder content is limited to between 10 wt% and 20 wt% of the total mass. This mass ratio is set to ensure that the paste solder has suitable viscosity and flowability, facilitating precise coating and positioning, while avoiding excessive binder content leading to dilution of the effective components of the solder, or excessive binder content leading to poor paste stability and difficulty in molding. Specifically, the amount of binder added can be finely adjusted by accurately weighing the solder powder and binder, combined with rheological testing, to optimize the thixotropy and adhesion of the paste solder, ensuring it maintains its shape during application while melting smoothly upon heating. The selected binders include one or more of rosin-based gum, cellulose-based gum, terpineol, and anhydrous ethanol. The selection of these binder components is based on their volatility characteristics during soldering and their impact on solder performance. For example, rosin-based gum can be used alone as a binder, as it volatilizes effectively during heating, reducing residue contamination of the solder interface; alternatively, a composite binder system can be used, such as a mixture of cellulose-based gum, terpineol, and anhydrous ethanol. Cellulose-based adhesive provides the main bonding effect and paste skeleton, terpineol, as a high-boiling-point solvent and flux, helps to adjust the viscosity of the paste and promote the wetting of the brazing filler metal, while anhydrous ethanol, as a volatile solvent, is used to adjust the consistency and drying speed of the paste, ensuring that the adhesive can be cleanly decomposed and volatilized at the brazing temperature without affecting the metallurgical bonding performance of the brazing filler metal.
[0071] In this optional embodiment, by preparing the brazing filler metal for ceramic-high-temperature alloy welding into a paste form and precisely controlling the content and type of adhesive, uniform and precise application of the brazing filler metal during the welding process is achieved. In the welding method, when the ceramic, the brazing filler metal, and the high-temperature alloy are placed in a vacuum environment and heated, the paste-like brazing filler metal can uniformly fill the interfacial gap between the ceramic and the high-temperature alloy, avoiding the problems of uneven or misaligned placement of traditional solid brazing filler metal. During the heating process in steps S1 and S2 (i.e., heating at a rate of 8°C / min to 15°C / min to 300°C to 500°C and holding for at least 10 minutes, and continuing heating to the brazing temperature and holding until the brazing filler metal melts), the adhesive gradually decomposes and volatilizes. Its content is precisely controlled within the range of 10 wt% to 20 wt%, ensuring that the adhesive provides sufficient viscosity while being cleanly removed, minimizing the interference of residues on the melting and flow of the brazing filler metal. The selected rosin-based adhesive, cellulose-based adhesive, terpineol, and anhydrous ethanol binders possess excellent thermal decomposition characteristics, ensuring complete volatilization at brazing temperatures. This creates favorable conditions for the full reaction of the face-centered cubic high-entropy alloy-based brazing filler metal and the second-phase brazing filler metal, thereby generating whiskers in situ. This paste-like brazing filler metal application method combines the phase separation characteristics, thermal expansion coefficient, and melting point differences of the filler metal itself with the characteristic of generating whiskers in situ during the welding process. This allows the filler metal to better wet the ceramic and high-temperature alloy surfaces, promote metallurgical bonding, effectively alleviate residual thermal stress caused by thermal expansion mismatch, and inhibit harmful interfacial reactions and the formation of brittle phases, thereby improving the joint strength and service stability.
[0072] The present invention will be further described below with reference to specific embodiments.
[0073] Example 1: AuCu-Ti+B solder was used to weld SiC ceramic to nickel-based superalloy GH3536.
[0074] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -6 (Tuo); 2. Apply a welding pressure of 0.5 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 400℃ at 10℃ / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 10℃ / min to the required brazing temperature (1100℃) for the low-melting-point brazing filler metal and hold for 30 min to melt the filler metal. Then, reduce the temperature to 20℃ at 10℃ / min and turn off the heating. Allow the furnace to cool to room temperature.
[0075] The microstructure of the joint was observed using an electron microscope, such as... Figures 2 to 4 As shown, Ti and B are generated in situ during welding, introducing a second phase, TiB, with a low coefficient of thermal expansion and a high melting point. The role of TiB is that its reduced coefficient of thermal expansion helps to create a gradient in the coefficient of thermal expansion of the weld, while the fine and dispersed distribution of the high-melting-point TiB helps to strengthen the joint at both room temperature and high temperature through the second phase bearing capacity and supporting a high-temperature skeleton. A shear test was performed on the joint, and the strength was 70 MPa.
[0076] Example 2: SiCf / SiC ceramics were welded to nickel-based superalloy GH3039 using CoCrFeNiCu-Ti+B solder.
[0077] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -4 (Tuo); 2. Apply a welding pressure of 1 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 300°C at 8°C / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 8°C / min to the required brazing temperature (1050°C) for the low-melting-point brazing filler metal and hold for 20 min to melt the filler metal. Then, reduce the temperature to 400°C at 5°C / min and turn off the heating. Allow the furnace to cool to room temperature.
[0078] The joint was subjected to a shear test, and the strength was 80 MPa.
[0079] Example 3: Cf / SiC ceramic was soldered to cobalt-based superalloy GH5188 using CuTi+NbB2 solder.
[0080] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -5 (Tuo); 2. Apply a welding pressure of 0.8 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 500℃ at 15℃ / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 10℃ / min to the required brazing temperature (1060℃) for the low-melting-point brazing filler metal and hold for 10 min to melt the filler metal. Then, reduce the temperature to 200℃ at 8℃ / min and turn off the heating. Allow the furnace to cool to room temperature.
[0081] The joint was subjected to a shear test, and the strength was 72 MPa.
[0082] Example 4: CuTi+W solder was used to weld SiC ceramic to nickel-based superalloy GH3536.
[0083] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -6 (Tuo); 2. Apply a welding pressure of 0.5 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 400℃ at 10℃ / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 10℃ / min to the required brazing temperature (1030℃) for the low-melting-point brazing filler metal and hold for 30 min to melt the filler metal. Then, reduce the temperature to 20℃ at 10℃ / min and turn off the heating. Allow the furnace to cool to room temperature.
[0084] The microstructure of the joint was observed using an electron microscope, such as... Figure 5 As shown, W exhibits its original state in the weld due to its high melting point. The low expansion and low melting point of the second phase helps improve the joint's temperature resistance and stress, thereby simultaneously enhancing the joint's room temperature and high temperature strength.
[0085] Comparative Example 1: AuCu-Ti solder was used to weld SiC ceramic to nickel-based superalloy GH3536.
[0086] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -6 (Tuo); 2. Apply a welding pressure of 0.5 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 400℃ at 10℃ / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 10℃ / min to the required brazing temperature (1000℃) for the low-melting-point brazing filler metal and hold for 30 min to melt the filler metal. Then, reduce the temperature to 20℃ at 10℃ / min and turn off the heating. Allow the furnace to cool to room temperature.
[0087] Backscattered electron micrographs (BSE images) of the connector were taken using a scanning electron microscope (SEM) with a backscattered electron detector (BSD / BSED), such as... Figure 6 (a) and Figure 6 As shown in (d).
[0088] Comparative Example 2: AuCu-Ti solder was used to weld SiC ceramic to nickel-based superalloy GH3536.
[0089] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -6 (Tuo); 2. Apply a welding pressure of 0.5 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 400°C at 10°C / min and hold for 10 min to allow terpineol to volatilize. Then, continue heating at 10°C / min to the required brazing temperature (1050°C) for the low-melting-point brazing filler metal and hold for 30 min to melt the filler metal. Then, reduce the temperature to 20°C at 10°C / min and turn off the heating. Allow the furnace to cool to room temperature.
[0090] Backscattered electron micrographs (BSE images) of the connector were taken using a scanning electron microscope (SEM) with a backscattered electron detector (BSD / BSED), such as... Figure 6 (b) and Figure 6 As shown in (e).
[0091] Comparative Example 3: AuCu-Ti solder was used to weld SiC ceramic to nickel-based superalloy GH3536.
[0092] 1. Place the ceramic base material, brazing filler metal, and metal base material in that order, clamp them with a mold, apply a pressure of approximately 50 g, and then place them in a vacuum furnace (vacuum degree 5×10). -6 (Tuo); 2. Apply a welding pressure of 0.5 MPa to the assembled sample to prevent the sample from moving during the brazing process; 3. To begin welding, heat to 400℃ at 10℃ / min and hold for 10 min to allow terpineol to volatilize. Then continue heating at 10℃ / min to the required brazing temperature (1100℃) for the low-melting-point brazing filler metal and hold for 30 min to melt the filler metal. Then reduce the temperature to 20℃ at 10℃ / min and turn off the heating. Let the furnace cool to room temperature.
[0093] The joint was subjected to a shear test, and the strength was 40 MPa. Compared with Example 1, the joint strength increased from 40 MPa to 70 MPa, showing a significant improvement.
[0094] Backscattered electron micrographs (BSE images) of the connector were taken using a scanning electron microscope (SEM) with a backscattered electron detector (BSD / BSED), such as... Figure 6 (c) and Figure 6 As shown in (f).
[0095] In Comparative Example 1, the weld seam of the joint contains Mo-rich phases, TiNi3, and Ni2Si, which are brittle and prone to aggregation. The Mo-rich phase is primarily a ternary phase (Mo-rich phase) formed by the dissolution of Mo from the base metal, not an additional addition. In Comparative Example 2, compared to Comparative Example 1, the brazing temperature is increased, promoting element diffusion and reaction, resulting in brittle phases in the weld seam. In Comparative Example 3, the brazing temperature is further increased, leading to more complete element diffusion and intensified reaction. This results in an increase in large, continuous intermetallic compounds such as TiNi3 and Ni2Si in the weld seam, coarsening of the weld microstructure, and a significant increase in the proportion of brittle phases, leading to decreased joint toughness and increased brittle fracture. In Comparative Examples 1 to 3, no whiskers are formed between the ceramic and the high-temperature alloy to act as a barrier, and the reaction between the base metal and the brazing filler metal is uncontrollable, resulting in unstable joint quality.
[0096] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.
Claims
1. A solder for welding ceramics and high-temperature alloys, characterized in that, The solder includes a face-centered cubic high-entropy alloy-based solder with phase separation characteristics and a second-phase solder. The thermal expansion coefficient of the face-centered cubic high-entropy alloy-based solder is higher than that of the second-phase solder, and the melting point of the face-centered cubic high-entropy alloy-based solder is lower than that of the second-phase solder. The face-centered cubic high-entropy alloy-based solder and the second phase solder undergo an in-situ reaction during the soldering process to generate whiskers; wherein the face-centered cubic high-entropy alloy-based solder includes one or more of Ti and V, and the second phase solder includes one or more of B, Si and C.
2. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The face-centered cubic high-entropy alloy-based brazing filler metal and the second phase brazing filler metal are uniformly mixed by vacuum arc melting or laser melting.
3. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The face-centered cubic high-entropy alloy-based solder includes one or more of AuCu-Ti, CuNi-Ti, AuCu-V, CuNi-V, Cu-Ti, and CoCrFeNiCu-Ti.
4. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The second phase solder includes one or more of B, SiC, and NbB2.
5. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The whiskers include one or more of TiB whiskers, TiC whiskers, Ti5Si3 whiskers, (Ti,Nb)B2 whiskers, VB2 whiskers, VB whiskers, V3Si whiskers, VSi2 whiskers, VC whiskers, and (V,Nb)B2 whiskers.
6. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The second phase solder also includes one or more of Mo and W.
7. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 6, characterized in that, The whiskers also include one or more of Mo2TiB2 whiskers, W2TiB2 whiskers, TiMoB whiskers, TiWB whiskers, Mo2V8B2 whiskers, and W2V8B2 whiskers.
8. The brazing filler metal for welding ceramics and high-temperature alloys according to claim 1, characterized in that, The mass ratio of the face-centered cubic high-entropy alloy-based solder to the second phase solder is 90:10 to 70:
30.
9. A method for welding ceramics to high-temperature alloys, characterized in that, Includes the following steps: S1: Take the brazing filler metal for welding ceramics and high-temperature alloys as described in any one of claims 1-8, place it in a vacuum environment in the order of ceramics, brazing filler metal and high-temperature alloy, heat it to 300°C to 500°C at a heating rate of 8°C / min to 15°C / min and hold it at that temperature for more than 10 minutes. S2: Continue heating at a heating rate of 8 ℃ / min to 15 ℃ / min to the brazing temperature and hold at that temperature until the brazing filler metal melts; S3: Cool down to 20°C to 400°C at a rate of 5°C / min to 10°C / min, and then furnace cool to room temperature.
10. The welding method for ceramics and high-temperature alloys according to claim 9, characterized in that, The brazing filler metal for welding ceramics and high-temperature alloys is prepared into a paste using an adhesive, wherein the adhesive accounts for 10 wt% to 20 wt% of the total mass of the paste brazing filler metal, and the adhesive includes one or more of rosin-based gum, cellulose-based gum, terpineol, and anhydrous ethanol.